The value of European exchange programs for early career family doctors. Issue 4 (4th July 2017) - Bridgwood, Bernadeta; Willoughby, Hannah; Attridge, Madeleine; Tang, Eugene
Abstract: The Hippokrates Exchange programme (HEP) is designed to give early career General Practitioners (Associates in Training (AITs)/First5s) first-hand experience into concepts of a primary healthcare system outside of their host country. The aim is to improve GP knowledge and skills, inspire professional development and promote a global approach to primary care. Although an increasing number are taking up this opportunity, their views and experiences of international exchanges are not well described. The aim of the study was to explore the experiences of AITs/First5s following their HEP exchanges. This qualitative study analysed 16 post-exchange reports of UK participants visiting 10 European countries via the HEP, using a thematic approach. Participants were unanimously positive about their exchange experiences. The themes that emerged were (1) Comparison of primary care practice (2) Infrastructure of host primary care (3) Motivation and experience of exchanges and (4) Learning and reflection. Participants displayed considerable benefits from these exchanges by broadening their experience in different primary care systems and identifying improvements to be incorporated into their UK practice.